THE USE OF SOCIAL MEDIA FOR NEW COLLEGE STUDENT DEVELOPMENT PROCESS - Haq, Alam Asrorul; Maulana, Aris; Ramadhana, Dimas; Deboraa, Dyanrosa; Anugrah, Prananda (Letters in Information Technology Education (LITE), 2018)
This study was conducted to examine how the use of social media to developing a new college student at State University of Malang. This study uses in-depth interviews method were conducted in a manner that has been structured. This method applied to eight new college students to get information from students about the new college student development through social media. All the students in this case, uses social media Whatsapp and Instagram in their development process, only a few students who use LINE and Facebook. This study focuses on three things that is how social media is used to perform a new student development, student response in development through social media and the tendency of students to choose development process through social media or directly development process. The results of this study can be obtained that social media help in the process but the given information must be complete and clear.